The Application of Integrated Pest Control Management in Raw Materials for The Animal Feed Industry at PT. XYZ Unit Buduran - Badriah, Lailatul; Hadiena, Avicena Darling; Cahyaningrat, Thalita Rizki Mirzanda; Rozci, Fatchur (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Integrated Pest Control Management (IPCM) is a crucial strategy for companies to mitigate pest attacks on raw materials, thereby preventing financial losses. This study was conducted at PT. XYZ, Unit Buduran, Sidoarjo District, an animal feed production company, to identify effective pest control strategies. Using a descriptive analysis method, primary and secondary data were collected to evaluate existing practices. The findings revealed that PT. XYZ employs various pest control strategies, including spraying, fogging, glue traps, yellow traps, ultrasonic sound technology, and temperature and humidity monitoring. These integrated strategies reflect the company's commitment to minimizing pest-related risks and maintaining raw material quality. The study highlights the importance of combining traditional and innovative methods for effective pest management in the animal feed industry. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 12: Responsible Consumption and ProductionGoal 15: Life on Land